Narrativa y narración en el relato audiovisual: apuntes para la distinción de forma y contenido (Tema Central) - Ordóñez Revelo, Gonzalo Javier (2018)
In the main, the audiovisual narrative concept covers any production that contains a sequence of images and sounds, which results in confusion with the concept of narration. The distinction lack of the two concepts has difficulties analysis as a consequence, in the field of communication, of the different forms of audiovisual production that now have an infinity of formats and styles. One way of contributing to the conceptual distinction is through the matching the form categories and content with the narrative and narration, respectively, in order to provoke a better articulation of the interpretation. Since the source of any narrative is in the cinematographic language, this work is based on the analysis of several films, emphasizing the cinema of martial arts as a particularly illustrative case.